Effect of Mechanical Vibration with Different Frequencies on Pore Structure and Fractal Characteristics in Lean Coal. (22nd September 2021) - Shen, Maoliang; Chen, Xuexi; Xu, Yong
Abstract : The mechanical vibrations caused by underground operations can easily lead to coal and gas outbursts in coal mines. Using the MVGAD-I experimental platform that we designed, the raw coal (0 Hz) was treated with vibration frequencies of 25, 50, 75, and 100 Hz, and the coal samples with different frequency vibrations were obtained. The total pore volume (TPV), specific surface area (SSA), pore size distribution, and the pore fractal dimension (PFD) of five coal samples were analyzed by mercury intrusion porosimetry and low-pressure nitrogen adsorption data. We found that the TPV, SSA, and PFD of the coal samples fluctuate with the increase of vibration frequency. The changes of the TPV and SSA of coal samples treated with 25 and 75 Hz vibrations were significantly greater than those subjected to vibrations of 50 and 100 Hz. Compared with the raw coal (0 Hz), the TPV and SSA of macropores, mesopores, and micropores increased the most in 75 Hz vibration coal sample. Therefore, the 75 Hz vibration excitation can improve the permeability of a body of coal mass and is conducive to the diffusion and seepage of coalbed methane and its production.. The influence of 25 Hz vibration on the TPV and SSA of macropores and mesopores is not obvious, but the TPV and SSA of minipores and micropores decrease significantly, which is not conducive to gas diffusion and adsorption. In addition, 25 and 75 Hz vibrations obviously damaged the fractal characteristics of both mesopores and micropores, resulting in the change of gas adsorption and diffusion ability. The rational use of a 75 Hz vibration is beneficial to both the production of gas and the prevention of outbursts, while a 25 Hz vibration should be avoided. The results are expected to reveal the microscopic mechanism of a vibration-induced outburst and provide theoretical guidance for employing the appropriate frequency of vibration to improve the rate of gas drainage and reduce the risk of outbursts.